Mammary artery Doppler ultrasonography of Brazilian Bergamasca dairy ewe lambs under the influence of two different feeding plans - Dantas, Ariane [UNESP]; Siqueira, Edson R. [UNESP]; Fernandes, Simone [UNESP]; Oba, Eunice [UNESP]; Machado, Vânia M.V. [UNESP]; Castilho, André M. [UNESP]; Sartori, Márcia M.P. [UNESP]; Santos, Roberta V. [UNESP] (FapUNIFESP (SciELO), 2017)
Blood supply of mammary gland is extremely important, since it is a crucial factor in the mammary tissue development. The objective of this study was to describe and assess main mammary artery hemodynamic characteristics of lambs with two growth rates, using Doppler ultrasound. Two experimental groups, A and B, (n=10) of female Brazilian Bergamasca lambs were kept under the same management conditions and facilities. There were two phases: Phase 1, from 90 days of age until onset of puberty; Phase 2, from puberty until 1 year of age. During phase 1, a specific diet was formulated to each experimental group to obtain two different average daily gains: 150g, for treatment A, and 250g, for treatment B. During phase 2, there was no difference on the diet offered to both groups. Every 14 days, all animals were weighed and their body condition score was evaluated. Every 60 days, ultrasound exams (Doppler) of mammary artery were performed to obtain resistance and pulsatility indexes. Treatment B lambs showed higher weight gain and higher body condition score (P < 0.05). However, for resistance and pulsatility indexes, there was no difference between treatments (P > 0.05). Hemodynamic values remained constant, independent of diet or body development presented by the animals. Obtained data is valuable information on Bergamasca ewe lambs development.
Keywords: Blood flow; Brazilian Bergamasca; Dairy ewes; Dairy lamb; Doppler; Feeding plans; Mammary artery; Nutrition; Ultrasonography; Ultrasound